Marine Pollution 73/ 78 IMO convention: a tool for sustainable marine resources in Kepulauan Riau Province - Zacky Abdurrahman (EDP Sciences, 2021)
Annual sludge oil mitigation in Kepulauan Riau is one of the government’s efforts to comply with the results of the Convention of Marine Pollution (MARPOL) 73/ 78 IMO which is well-known as the basis of efforts to prevent pollution at ocean caused by economic activities at sea. This research aims to observe and evaluate the government effort to comply with the MARPOL 73/ 78 convention and its annual implementation response and mitigate illegal sludge oil activity in Kepulauan Riau Province. The data collection was carried out by sampling method to contaminated areas in Batam and Bintan as a locus of the research. Analysis of Green Theory, in the discipline of International Relations, conducted to provide a spotlight on environmental aspects in a sludge oil occurrence. The understanding of the concept of triangulation between environmental, economic, and state aspects is the basis for understanding the sludge oil issue, which is trying to be described through the perspective of global environmental ethics. It is shown that the overall efforts made by the government are in accordance with the MARPOL 73/78 and environmental analysis based on Green Theory. In conclusion, upcoming mitigation to be improved are appropriate budgeting, technology to response and prevent the occurrence, socialization and empowering coastal local communities, and optimizing regional collective responsibility and cooperation